100 UMPSA volunteers help make Plogging@Pantai Tanjung Gosong a success - Nor Salwana, Mohammad Idris (UMPSA, 2025)
PEKAN, 23 July 2025 – Nearly 100 volunteers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Pos Malaysia Berhad Pahang, SWCorp, and Alam Flora came together to make the Plogging@Pantai Tanjung Gosong Programme a resounding success.